(untitled) (Journal of the College of Basic Education, 2022)
One of the important reasons for choosing the subject of the research is the role that sculpture can play as a stand-alone plastic art by contributing to raising the level of artistic and aesthetic taste for children. And what this leaves a positive impact on their behavior in daily life